THE EFFECT OF CREDIT PROVISION AND CREDIT RISK ON RETURN ON EQUITY (ROE) AT PT BANK SULSELBAR MAKASSAR CITY - Auliyah Nurwafiyyah; Andi Sri Kumala Putri P; Fakhruddin Kurnia (Universitas Ichsan Sidenreng Rappang, 2022)
Auliyah Nurwafiyyah. 2018. The Effect of Credit Provision and Credit Risk on Return On Equity (ROE) at Bank Sulselbar. Supervisor : Suriyanti and Munawir Nasir. This study aims to examine the effect of lending and credit risk having a significant impact on Return On Equity (ROE) in banking companies in South Sulawesi. The data in this study was obtained from the financial statements of banking companies in South Sulawesi. This study uses secondary data by making observations by visiting the Capital Market Information Center (PIPM). The data analysis method used is multiple linear regression analysis using a Likert scale with the help of SPSS analysis. The results showed that partially, the provision of credit has a positive and insignificant effect on Return On Equity (ROE). In contrast, credit risk has a negative and significant impact on Return On Equity (ROE). Simultaneously, credit and credit risk affect Return On Equity (ROE).